Targeting Setdb1 in T cells induces transplant tolerance without compromising antitumor immunity - Xiaosheng Tan; Xiangli Zhao; Zunsong Hu; Ding-Sheng Jiang; Zhibo Ma; Lingjuan Sun; Jingzeng Wang; Xia Huang; Bin Xie; Mi Wu; Min Ma; Cong-Yi Wang; et al. (Nature Communications)
Abstract Suppressing immune responses promotes allograft survival but also favours tumour progression and recurrence. Selectively suppressing allograft rejection while maintaining or even enhancing antitumor immunity is challenging. Here, we show loss of allograft-related rejection in mice deficient in Setdb1, an H3K9 methyltransferase, while antitumor immunity remains intact. RNA sequencing shows that Setdb1-deficiency does not affect T-cell activation or cytokine production but induces an increase in Treg-cell-associated gene expression. Depletion of Treg cells impairs graft acceptance in Setdb1-deficient mice, indicating that the Treg cells promote allograft survival. Surprisingly, Treg cell-specific Setdb1 deficiency does not prolong allograft survival, suggesting that Setdb1 may function prior to Foxp3 induction. Using single-cell RNA sequencing, we find that Setdb1 deficiency induces a new Treg population in the thymus. This subset of Treg cells expresses less IL-1R2 and IL-18R1. Mechanistically, during Treg cell induction, Setdb1 is recruited by transcription factor ATF and altered histone methylation. Our data thus define Setdb1 in T cells as a hub for Treg cell differentiation, in the absence of which suppressing allograft rejection is uncoupled from maintaining antitumor immunity.